PENGARUH DISIPLIN KERJA TERHADAP KINERJA CLEANING SERVICE DI PT. CERAH SINERGI SEJAHTERA - Muhammad Riki Sungkono (Universitas Bina Taruna Gorontalo, 2024)
This study aims to determine whether there is an influence of work discipline on employee performance at PT. CSS in the field of Cleaning Service. The approach in this research is descriptive quantitative. The sample in this research is all Cleaning Service employees at PT. Cerah Synergies Prosperity, totaling 50 people. The data collection technique in this study was a questionnaire. The results showed that there was a significant influence between work discipline on employee performance with a tcount value of 8,887 with a significance level of 0.000 <0.05, this shows that work discipline has a positive effect on employee performance because the tcount value is greater than the ttable value and the level significance < (0.05) so that it can be stated to have a positive effect. Based on the test results of the coefficient of determination, R square has a value of 0.617 or equal to 61.7%. This figure can be used to see the magnitude of the influence of work discipline on employee performance, while the remaining 39.3% is influenced by other variables outside the regression equation or variables not examined, for example promotions, brand image and purchasing decisions.